Critical micelle concentration of tridecane, tetradecane and hexadecane phosphonic acids and their mono- and disodium salts - Di Anibal, Carolina Vanesa (2009)
The critical micelle concentration (CMC) of tridecane, tetradecane and hexadecane phosphonic acids and their mono- and disodium salts were determined with a battery of methods. The CMC values for all the studied species follow the general trend of those of the lower homologos of the series. The values of the Gibbs free energy of micellisation are interpreted on the basis of the micelle structure in salts and acids. The monolater formed by acids at the air/water interface at the CMC is compact, which may be explained by the union among the polar head groups by hydrogen bonds. Monsodium salts show premicellar formation of acid soap-like compounds. The micellisation of disodium salts is accompanied by strong hydrolisis.